Sharia Branding in Housing Context: A Study of Halal Lifestyle Representation - Putri, Addin Kurnia; Sunesti, Yuyun (JSW (Jurnal Sosiologi Walisongo), 2021)
Sharia housing has mushroomed in Indonesia in recent years. It offers a different concept of housing as the developers claim to be following Islamic values. This study analyzes how Sharia housing advertisements on social media, especially Instagram, represent the halal lifestyle. The method used in this research was a semiotic approach to analyze the signs of Sharia housing ads in the realm of digital media and its meanings. The study results show that Sharia housing advertising on social media has commodified the halal concept of Sharia-based housing. The term â€œhalal houseâ€ was also used to signify the meaning of Sharia image symbols that distinguished it from other housing. Sharia brands were also represented in advertising languages and the visualization of symbols displayed. These ads represented the halal concept not only as an image but also as a lifestyle. The halal lifestyle relating to Sharia housing has become a new trend in the Muslim communities constructed through religious symbols in Sharia housing advertisements.